Coronavirus disease 2019 and severe asthma. Issue 2 (20th April 2023) - Benfante, Alida; Pirrello, Giuseppe; Sala, Francesca; Seminara, Gabriele; Scichilone, Nicola
Abstract : Purpose of review: The relationship between severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and the most severe forms of asthma has been an object of discussion. Indeed, it is not clear whether asthma is among the risk factors for the occurrence of severe coronavirus disease 2019 (COVID-19) disease, or rather it plays a protective role against the worsening of the respiratory involvement in the SARS-CoV-2 infection. On the other hand, the extent to which coronavirus infection may trigger asthma attacks is still partly unknown. The current investigation aims at reviewing the available literature on the topic to address factors influencing this relationship. Recent findings: Based on recent observations, it is likely that type 2 inflammation plays a protective role against SARS-CoV-2 infection and disease. In particular, asthmatics show different expression of angiotensin-converting enzyme2 (ACE2) and Transmembrane protease, serine 2 (TMPRSS2) that are responsible for a reduced risk of infection as well as lower risk of hospitalization. Interestingly, studies showed a safe profile of inhaled corticosteroids and biological drugs in SARS-CoV-2 infection. In addition, inhaled corticosteroid could play a protective role against worsening of asthma. Summary: The current findings suggest that current treatment for asthma should be maintained to avoid severe exacerbations. Severe asthmatics under biological treatment should continue their medications, and be encouraged to receive COVID-19 vaccines.